Aspectos ergonômicos do posto de trabalho de um trator-subsolador na implantação florestal - Figueiredo, Ana Paula Micali (2017)
The operations for preparing the soil in the forest implantation are mainly carried out with machines adapted from agriculture, which may offer inadequate ergonomic conditions to the operators in terms of the working place size, body posture and environmental factors. This study aimed at performing an analysis of some ergonomic aspects in the subsoiler working place with the purpose of contributing to improve the conditions referred to as comfort, safety, health and quality of life of the operators. The study was carried out in the forest implantation operational areas in a company located in the municipality of Arapoti, state of Paraná, and embraced 10 operators of a subsoiler. The ergonomic analysis included the access and seat dimensions of the subsoiler working place, in compliance with the ABNT standards 4252 (2011) and 4253 (2015), respectively. The seat dimensions were also compared with the anthropometric data of the operators from the region. Cameras were installed inside the machine for the postural analysis; the images were visualized with the MSSHOW software and analyzed by using the Rapid Entire Body Assessment (REBA), in addition to the Rapid Upper Limb Assessment (RULA). The human factors, working conditions and postural discomfort were obtained through individual interviews with the operators by using Pearson's correlation (r) in order to test the variables of the human factors. Finally, an analysis of the operators’ occupational exposure to noise was performed with the use of a dosimeter; the noise doses with the machine stereo system on and off were obtained, and, then, the results were compared with the Regulatory Norm NR 15. The findings showed that for opening the access and emergency exits, all measures were in accordance with the standards, whereas in relation to the seat dimensions, only the backrest height and the seat width were in conformity. When comparing the seat dimensions with the anthropometric data it was seen that the majority of the tractor seat measures were not in agreement with the anthropometric data of the operators. Considering the postural analysis, two typical postures that had been adopted by the operators for executing the work were found. Such postures showed a biomechanical risk caused by the trunk and neck rotation, in addition to the repetitive movements of the hands and wrists, and the permanence for long periods in the static position (25.5%). The variables of the human factors showed a low correlation among themselves, except for the stature that had a mean correlation with the variables known as knees and lower back. The map of the body segments indicated discomfort in the region of the hands, shoulders, arms, wrists, knees, calves, ankles, feet, lower back and neck, which were justified by operators due to the repetitive movements and inappropriate postures during work. Regarding noise, 85 dB (A) levels were found with the stereo system on, and 76 dB (A) when it was off, thus, this was within the acceptable maximum daily exposure level.